Hyperactivity of the Inferior Oblique Muscle in the Human Eye: Histopathological Study - A. Ali, Ali Hassan (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Awareness of the impact of the various surgical treatments requires an awareness of a slightly different architecture of the inferior oblique (IO) muscle in comparison to the other extraocular muscles. The IO muscle’s anatomy has been linked to particular clinical diagnoses in a number of investigations. Aims of Study: To establish a correlation between the various levels of clinical overaction and the histological alternations of the IO muscle. Materials and Methods: Once the clinical severity of the muscle over-action was established, 10 samples from the IO muscles were obtained during the strabismus surgery. As a control, one muscle biopsy was obtained during enucleation surgery. A light microscope was used to examine each biopsy. Results: Grade II and grade III IO overaction revealed numerous histological abnormalities under light microscopy, including fibro-fatty infiltrations, nerve bundle enlargement, muscle fiber degeneration, and varied muscle fiber size. Fatty infiltration, mononuclear infiltration, and perimysium and endomysium fibrosis were observed in grade III IO overaction. Conclusion: The clinical stages of muscle overaction are correlated with histopathological alterations in the IO muscle.